(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an in-depth exploration of cooling systems in transformers. The article categorizes transformer cooling systems into air-cooled and oil-cooled types, further detailing subcategories like natural and forced cooling methods (e.g., ONAN, ONAF, OFAF, OFWF). Advanced cooling technologies such as directed oil cooling, gas cooling, water spray cooling, and heat pipe cooling are also discussed, highlighting their applications in specialized and high-capacity transformers.